2013
DOI: 10.1161/jaha.113.000191
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin‐L Ameliorates Cardiac Hypertrophy Through Activation of the Autophagy–Lysosomal Dependent Protein Processing Pathways

Abstract: BackgroundAutophagy is critical in the maintenance of cellular protein quality control, the final step of which involves the fusion of autophagosomes with lysosomes. Cathepsin‐L (CTSL) is a key member of the lysosomal protease family that is expressed in the murine and human heart, and it may play an important role in protein turnover. We hypothesized that CTSL is important in regulating protein processing in the heart, particularly under pathological stress.Methods and ResultsPhenylephrine‐induced cardiac hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
46
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 47 publications
(52 reference statements)
5
46
0
2
Order By: Relevance
“…We have previously reported that expression of SCCA1 leads to a suppression of both lysosomal and proteasomal protein turnover, in a manner that requires its protease inhibitory activity (13). Although the precise mechanism underlying this SCCA1-mediated blockade of protein turnover remains to be determined, our finding is in line with a recent report that the cathepsin L-deficient cells display impaired lysosomal turnover, accumulation of ubiquitinated proteins and protein aggregates, and disrupted ER homeostasis (45). It is conceivable that the blockade of protein turnover can lead to UPR, which we show here promotes pro-tumorigenic IL-6 production.…”
Section: Discussionsupporting
confidence: 91%
“…We have previously reported that expression of SCCA1 leads to a suppression of both lysosomal and proteasomal protein turnover, in a manner that requires its protease inhibitory activity (13). Although the precise mechanism underlying this SCCA1-mediated blockade of protein turnover remains to be determined, our finding is in line with a recent report that the cathepsin L-deficient cells display impaired lysosomal turnover, accumulation of ubiquitinated proteins and protein aggregates, and disrupted ER homeostasis (45). It is conceivable that the blockade of protein turnover can lead to UPR, which we show here promotes pro-tumorigenic IL-6 production.…”
Section: Discussionsupporting
confidence: 91%
“…If this system is compromised, impaired protein degradation and abnormal protein accumulation may result in not only cellular dysfunction but also organ failure including cardiomyopathy [17]. The participants in the present study had higher levels of CatL than patients with cardiovascular disease [18], and higher levels of CatS than those reported by Job et al [19].…”
Section: Accepted Manuscriptsupporting
confidence: 41%
“…Previous studies have demonstrated that cathepsins are essential for both cardiomyocyte apoptosis (32) and extracellular matrix balance (22a, 29). Further studies have revealed increased cathepsin activity in both hypertrophic and failing hearts (8,31) and showed that cathepsins are regulated under these pathological conditions. CTSB (GenBank Accession No.…”
mentioning
confidence: 99%